2017
DOI: 10.1016/j.foodres.2017.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Combination of selected enzymes with cetyltrimethylammonium bromide in biofilm inactivation, removal and regrowth

Abstract: Enzymes are considered an innovative and environmentally friendly approach for biofilm control due to their lytic and dispersal activities. In this study, four enzymes (β-glucanase, α-amylase, lipase and protease) were tested separately and in combination with the quaternary ammonium compound cetyltrimethylammonium bromide (CTAB) to control flow-generated biofilms of Pseudomonas fluorescens. The four enzymes caused modest reduction of biofilm colony forming units (CFU). Protease, β-glucanase and α-amylase also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
2
12
2
3
Order By: Relevance
“…However, when the biofilms of both bacteria were treated with the enzymatic product, the microbial load decreased significantly (2–2.5 log CFU cm −2 of reduction) compared to the biofilm growth achieved in 48 hr. Our results indicate a detachment of the cells adhered to the stainless steel caused by the enzymatic treatment, as reported by other authors (Araújo et al, ; Lequette, Boels, Clarisse, & Faille, ; Molobela, Cloete, & Beukes, ). The effectiveness of different enzymes on the detachment of different microorganisms in biofilms has also been thoroughly studied.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…However, when the biofilms of both bacteria were treated with the enzymatic product, the microbial load decreased significantly (2–2.5 log CFU cm −2 of reduction) compared to the biofilm growth achieved in 48 hr. Our results indicate a detachment of the cells adhered to the stainless steel caused by the enzymatic treatment, as reported by other authors (Araújo et al, ; Lequette, Boels, Clarisse, & Faille, ; Molobela, Cloete, & Beukes, ). The effectiveness of different enzymes on the detachment of different microorganisms in biofilms has also been thoroughly studied.…”
Section: Resultssupporting
confidence: 91%
“…sakazakii biofilms compared with at 45°C, which were similar to previous results obtained in this study. Furthermore, the figures obtained in this study were higher than those obtained by Araújo et al (), who reported that enzymatic treatments with a single enzyme, including protease, β‐glucanase and α‐amylase caused a modest elimination of P . fluorescens biofilms with a reduction ranging from 1 to 1.5 log CFU cm −2 .…”
Section: Resultscontrasting
confidence: 82%
See 3 more Smart Citations